Spontaneous Symmetry Breaking and the Cosmological Constant - Gamboa-Rios, J; Mendez-Ferrada, F; Tapia-Arellano, N (World Scientific, 2023)
An approach that allows studying the relationship between the neutralization of the cosmological constant and instantons for cosmology coupled to antisymmetric elds is proposed. Using suitable variables, the Lagrangian leading to the FRW equations can be written analogously to a Ginzburg-Landau theory, and we show how spontaneous symmetry breaking appears. © 2023 World Scientific. All rights reserved.